Susceptibility of periodontal pathogens to a novel target-specific drug delivery system containing self-nanoemulsifying curcumin: An in vitro study - Veena HR; Riya Achamma Daniel; Ashwin Prabhu; Shilpa P; Suman Basavaraju (Journal of Advanced Periodontology and Implant Dentistry)
Background. Long-term use of many classic chemotherapeutic agents as adjuncts in the management of periodontitis has adverse complications, leading to seeking out naturopathic remedies. Although curcumin has been investigated in managing periodontitis, its therapeutic benefits have not been fully explored due to its limited solubility in an aqueous medium. This study aimed to develop a novel target-specific drug delivery system containing 1% self-nanoemulsifying curcumin (SNEC) in a hydroxypropylmethylcellulose (HPMC) matrix and evaluate the susceptibility of periodontal pathogens to this system in vitro. Methods. Its antibacterial activity against Tannerella forsythia, Porphyromonas gingivalis, Prevotella intermedia, and Aggregatibacter actinomycetemcomitans was evaluated and compared to pure nano-curcumin and SNEC alone by estimating their minimum inhibitory concentrations (MIC). Results. The antibacterial activity of pure nano-curcumin, SNEC, and SNEC in HPMC against the four periodontal pathogens evaluated in terms of MIC was recorded in the range of 0.2‒0.4, 0.4‒0.8, and 0.2‒0.8 µg/mL, respectively. However, the MIC of all three curcumin formulations against the periodontal pathogens tested was higher than that of the standard moxifloxacin. While both pure nano-curcumin and SNEC showed increasing values of inhibition zones with increasing concentrations on disk diffusion assay, lower concentrations of SNEC in HPMC did not show a zone of inhibition against the tested pathogens. Conclusion. The novel delivery system containing SNEC in HPMC may be a potential adjunct in managing periodontitis due to its probable sustained antimicrobial activity against the tested periodontal pathogens.